PENGELOLAAN AIR, BAHAN ORGANIK DAN VARIETAS ADAPTIF UNTUK MENINGKATKAN HASIL PADI DI LAHAN RAWA PASANG SURUT - Koesrini Koesrini; Khairil Anwar (Research Center for Biology-Indonesian Institute of Sciences, 2017)
Iron toxicity is a factor causing low rice yield on tidal swamp land (TSL).Soil quality improvement by using water management, organic matter and introducing adaptable varietywere some options to increaseits productivity in the soils. Field experiment was conducted to evaluate effects of applying water management, organic matter and adaptable variety to increase its productivity on a TSL of KP Belandean, Barito Kuala District of South Kalimantan, during dry season of 2010. The research was arranged in a split-split-plot design with three replicates. The main plots were two water management, i.e: P0 = without water management (control) and P1= intermittent water management, while sub plots were three organic matter application, i.e: B0 = without organic matter application (control), B1 = straw compost 3 t/ha, B2 = manure 2 t/ha, and sub sub plots were five rice varieties, i.e. V1 = Mekongga, V2 = Inpari 1, V3 = Ciherang, V4 = Silugonggo and V5 = Margasari. The result showed that there was interaction between water management and variety tested on rice yield in TSL. The highest yield was reached by Inpari 1 variety which treatment intermitten water management, with yield i.e. 5.390 t/ ha.Silugonggo and Ciherang was not suitable to cultivate on TSL. The implication of this research was variety recomendation on a tidal swamp land, i.e. Inpari 1 variety and intermitten water management.